Status and Problems of Counseling Psychology in the Modern World and Ukraine - Aleksandr Bondarenko; Nataliia Kucherovska; Svitlana Fedko (Психологічне консультування i психотерапія)
The article is devoted to the current state, problems and opportunities for the development of counseling psychology in Ukraine based on a comparative analysis of the functioning of this field in other countries of the world. An analysis of the current state of counseling psychology in countries with a developed tradition in this field belonging to different cultural and civilizational contexts was carried out. On the basis of the Cochrane methodology with the application of SWOT analysis, the results of the study of strengths and weaknesses, potential threats and prospects for the development of counseling psychology in eight countries of the world: Austria, India, Israel, Canada, France, the Republic of South Africa, Japan and Ukraine are summarized. It was established that counseling psychology in Ukraine not only does not lag behind other countries in terms of the number of practices and qualifications of specialists, but also has a number of advantages, such as the presence of a network of psychological consultations and higher educational institutions that train psychologists, the functioning of professional associations and periodicals, review Law on Psychological Assistance, etc. The growth in demand for the services of counseling psychologists in Ukraine in connection with military actions, as well as the expansion of the possibilities of conducting consultations in the online format, is analyzed. However, the problem of financing higher education was revealed, which leads to a decrease in the quality of professional training of psychologists; the problem of contradiction between consultative approaches and mental, religious and behavioral traditions of society is discussed; political and socio-economic factors are analyzed, such as impoverishment of the population, a decrease in its cultural level, which complicates the work of psychologists and limits access to psychological help.